PELAKSANAAN SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - Herna Novianti (Manajer Pendididikan, 2015)
The aim of this study generally to describe the implementation of Academic Supervision Principals in improving the performance of teachers at State Elementary School 62 Bengkulu City. The method used is descriptive qualitative research . Data collection techniques are observation , interviews and documentation. The conclusion of this study indicate that the implementation of academic supervision in elementary school principals 62 Bengkulu City hasimplemented management functions to help teachers develop the ability to manage the learning process to achieve the learning objectives in improving the performance of teachers .Keywords : academic supervision , principals , classroom teacher performance